ONLINE COOPERATIVE APPLICATION FOR COFFEE FARMER GROUP IN PAGAR ALAM CITY - Heriansyah Heriansyah; Putri Maharani (STMIK Pringsewu Lampung, 2019)
The city of Pagar Alam with the commodity of coffee plants with an area of 8,323 ha with a total production of 7,465.50 tons. The coffee plants produced by 90% of robusta types are the result of export commodities and have become a mainstay of the city's economy. Harapan Jaya farmer group located in Pagar Alam Utara sub-district, Pagar Alam City has a system of selling and marketing carried out individually through middlemen and not through coffee farmer groups. Marketing of coffee products to various cities through middlemen unwittingly has eliminated the distinctive characteristics and quality of Pagar Alam coffee because it has been processed and mixed with coffee from outside the city of Pagar Alam. The Participatory Action Research (PAR) model is used in this study as a research method approach, where researchers invite and involve coffee farmer groups as active participants in a concrete action where they themselves experience problems in order to change, improve, build and use a system built . The online cooperative application was built by collecting data related to the coffee sales system in Harapan Jaya coffee farmer group in the city of natural fences, then the researchers analyzed and designed the system based on existing data. Features in online cooperative applications can run well after implementation and testing. Deepening cooperative concepts that are more detailed such as adding business and other cooperative activities can be applied to online cooperative applications to further perfect this application.